2019
DOI: 10.1111/evo.13865
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and life‐history shape the evolution ofHeliconiuswings

Abstract: Phenotypic divergence between closely related species has long interested biologists. Taxa that inhabit a range of environments and have diverse natural histories can help understand how selection drives phenotypic divergence. In butterflies, wing color patterns have been extensively studied but diversity in wing shape and size is less well understood. Here, we assess the relative importance of phylogenetic relatedness, natural history, and habitat on shaping wing morphology in a large dataset of over 3500 ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 95 publications
(147 reference statements)
0
19
0
1
Order By: Relevance
“…Butterfly wing size varies according to the quality and quantity of the food source provided by larval host plants (Rodrigues & Moreira, 2004). It also varies according to the behavioral ecology of larvae and adults, as for example in lonely larvae, adults of the adult-mating clade and of higher altitudes, that have larger wings (Montejo-Kovacevich et al, 2019). In Heliconius butterflies, Müller (1912) showed through illustrations and text that the androconial scales of Heliconius apseudes (Hübner, [1813]), Heliconius eucrate (Godart, 1819) and Heliconius besckei Ménétriés, 1857, among other Nymphalidae, are quite variable on the upper surface of the hindwing, near the costal margin and particularly along the costal and subcostal veins.…”
mentioning
confidence: 99%
“…Butterfly wing size varies according to the quality and quantity of the food source provided by larval host plants (Rodrigues & Moreira, 2004). It also varies according to the behavioral ecology of larvae and adults, as for example in lonely larvae, adults of the adult-mating clade and of higher altitudes, that have larger wings (Montejo-Kovacevich et al, 2019). In Heliconius butterflies, Müller (1912) showed through illustrations and text that the androconial scales of Heliconius apseudes (Hübner, [1813]), Heliconius eucrate (Godart, 1819) and Heliconius besckei Ménétriés, 1857, among other Nymphalidae, are quite variable on the upper surface of the hindwing, near the costal margin and particularly along the costal and subcostal veins.…”
mentioning
confidence: 99%
“…The amount of wing shape variation explained by family across common-garden reared offspring was high for both species (H. erato: 21% and H. melpomene: 39%), especially when compared to the 74% of variance explained by species identity in a previous comparative study (Montejo-Kovacevich et al, 2019). The resemblance in wing aspect ratio between mothers and their offspring is indicative of a highly heritable trait (Fig.…”
Section: Wing Shape Is Heritablementioning
confidence: 71%
“…Generally, cases of wing shape plasticity are rarer than size plasticity, especially if the two traits are allometrically decoupled, allowing for subtle changes to be selected if advantageous (Carreira et al, 2011;Gilchrist & Partridge, 2001;Strauss, 1990). In Heliconius, wings have been found to be rounder at higher elevations, both across and within species that inhabit large ranges (Montejo-Kovacevich et al, 2019). In our study, wing shape differences observed in the wild in H. erato and H. melpomene were maintained in common-garden reared broods, with individuals from highland mothers having, on average, rounder wings (Fig.…”
Section: Wing Shape Is Heritablementioning
confidence: 99%
See 2 more Smart Citations